The 8th confession - Patterson, James 1947- (Patterson, James 1947- Women's murder club series, 2009)
The Women's Murder Club faces its toughest challenge as Detective Lindsay Boxer investigates the high-profile murder of two San Francisco millionaires and reporter Cindy Thomas digs into the brutal slaying of a preacher with a message of hope for the homeless.